Optimalisasi Biaya dan Waktu Proyek Kontruksi Pelebaran Jalan Menggunakan Earned Value - Sentot Tri Wibowo; Suwarno Suwarno; Ahmad Ridwan; Haris Wicaksono; Fitry Rahmawaty (Jurnal Manajemen Teknologi & Teknik Sipil, 2021)
In a construction project, there are several aspects that cause the project not to go according to plan. Cost and time are aspects that need to be considered to avoid losses incurred in a project. Jombang-ploso-legundi-gresik road project is one of the road widening projects carried out by PT. Mix Pro Indonesia. The project was carried out with the aim that access to (Surabaya-Mojokerto) or further trans Java toll road is quicker safe and smoother. This research aims to optimize the cost and time on the project using the Earned Value method. Calculations include the calculation of ACWP (Actual Cost of Work Performance), BCWS (Budgeted Cost Work Schedule), and BCWP (Budgeted Cost for Work Performed) using the Earned Value method. From these parameters, estimate aspects of cost and time. As well as project analysis of acceleration on a critical trajectory of work. The results of calculations in the 12th week obtained a BCWS value of Rp 1,216,677,846,400 BCWP = Rp 3,040,372,140,080, ACWP = Rp 3,678,560,000. CV value = -Rp 109,203,495.92, SV = Rp 895,646,816.82, CPI = 0.827, and for SPI = 2,499. From these results it can be seen that the CPI value < 1 which means that there are project expenditures that exceed the original plan. With the results, it can be used as a reference in the implementation of project activities.